Penerjemahan Kosakata Budaya pada Film Aruna dan Lidahnya - Adawiyah, Siti Lutfiah Rabiyatul; Ulfha, Siti Mutiah; Anwar, Saiful (ESENSI LINGUA, 2023)
The process of translating cultural terms is a challenging task that translators will face. This is because there is a possibility when a word or situation is not recognized in the target language. The purpose of this study is to describe the types of cultural vocabulary in the movie “Aruna dan Lidahnya”. The data is categorized using the padan method then continued with the sorting technique. Based on the results of the research data, 49 cultural vocabulary data were found which were categorized into 4 types. Material culture which includes food and place is the dominant type of vocabulary with a total of 29 data and a percentage of 61.70%. The form of cultural vocabulary in the material culture domain that appears a lot is food with a total of 25 data because the film focuses on the culinary. For the type of organization which includes religious and social organizations, there are 7 data with a percentage of 14.89%. For the type of gesture there are 6 data with a percentage of 12.76%. For socio-cultural types which include greetings, kinship and swearing, there are 5 data with a percentage of 10.63%. Literal translation and cultural equivalence procedures are used by the translator when the target language has the equivalent of the source language. Meanwhile, other procedures such as modulation, addition, transference, and couplet are used when the translator cannot find the equivalent in the target language.